Ultrasonic and thermodynamic effects of self-association of aliphatic alcohols in c-C6H12. I. Primary butanols - K. BEBEK; S. ERNST (Archives of Acoustics)
The ultrasound velocities in and densities of mixtures of n-butanol and isobutanol with cyclohexane as a common component have been measured at 293.15 K. The adiabatic compressibility coefficients. β_s = –1/V(∂V/∂p)_s, compressibilities, ϰ_s = β_sV, and the free intermolecular lengths, L, of those mixtures were estimated and their dependence on the alcohol concentration reproduced by simple polynomials. The excess values of the above quantities, V^E, β^E_s and ϰ^E_s were calculated and discussed. The dependence of those excess functions on the mixture composition, expressed in mole fractions of alcohol, x_1 can be successfully reproduced by the Redlich-Kister equation.